Quality Of Disclosure And Corporate Social Responsibility Reporting Practices In Indonesia - Eza Gusti Anugerah; Erwin Saraswati; Wuryan Andayani (Jurnal Akuntansi, 2018)
This research aims to analyze the influence of corporate social responsibility (CSR) reporting practices on CSR disclosure quality in Indonesia. This research used a sample of 103 companies across industries (except for natural resource companies) listed on Indonesian Stock Exchange from 2014 to 2016. This research found thatthe voluntary practice of stand-alone report, assurance and reporting guideline does not enhance the quality of disclosure.This practices tend to be usedas symbolic approach to fulfillcompanies legitimacy. This symbolic approach has the meaning that the companieswhich voluntarily disclose theirCSR information, merely aiming a positive impression from their stakeholders.Companies tend to disclose CSR information by diluting the relevant CSR information with unnecessary information to build their desired images.